PENGEMBANGAN BLOG SEBAGAI MEDIA PEMBELAJARAN UNTUK PEROLEHAN BELAJAR KONSEP KIMIA KARBON DI UNIVERSITAS MUHAMMADIYAH PONTIANAK - Mukhlishin, Hamdil; Umar, Syahwani; Tandililing, Edy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract : This study aims to (1) produce a valid learning blog as a medium of learning and practical learning in the acquisition of the concept of carbon chemistry, (2) to study the acquisition of carbon chemistry concepts using learning blog has been developed. The method used is the method of development, with the chosen design development using ADDIE development. Development steps are as follows: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Validation of product development include (1) expert test material, (2) test media expert, (3) lecturer of test subjects, (4) individual testing, (5) a small test group, and (6) of the test group . The instrument used in this study was a test, observation, questionnaires and document analysis. Results of this study indicate that (1) learning blog developed carbon chemistry has been declared valid and practical as media and learning resources in the acquisition of learned concepts carbon chemistry. (2) blog of learning that has been developed to help in the acquisition of learning the concept of carbon chemistry for students.Keywords: Developmental, Learning Blog, Carbon Chemistry